The Relationship Between Parenting Styles and Self-Harm Behavior in Adolescents - Yannavita Hadi Suwignyo; Nana Usnawati; Tutiek Herlina; Rahayu Sumaningsih (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Individuals are required to be able to adapt to the many changes that occur during adolescence, so support from the family is needed to deal with these changes. Normal development in this period of turmoil with rapid physical, cognitive and emotional transformations is influenced by parental interest and emotional involvement as well as parenting styles that determine the overall climate and communication in the family. Parents apply different parenting styles, ranging from authoritarian, democratic and permissive parenting. The purpose of this study was to determine the relationship between parenting patterns in adolescents and self-harm behavior in adolescents. This study was an analytic study with a case control design. The sample was 42 students of SMPN 1 Plaosan and their parents using a total population technique for the case group and a simple random sampling technique for control group. The independent variable was parenting style, the dependent variable was self harm behavior in adolescents. The instrument in this study used a questionnaire. To analyze the correlation used chi square test was used with α 0.05. The research results showed that most parents provided an authoritarian parenting style in the case group and some parents provided a democratic parenting style in the control group. The chi square test results obtained p = 0.00 (p = <0.05). The conclusion in this study is that there is a correlation between parenting patterns and self-harm behavior in adolescents. It is recommended that parents provide democratic parenting patterns for their children.